Dreamworlds of race empire and the utopian destiny of Anglo-America - Bell, Duncan 1976- (Princeton University Press, 2020)
How transatlantic thinkers in the late nineteenth and early twentieth centuries promoted the unification of Britain and the United StatesBetween the late nineteenth century and the First World War an ocean-spanning network of prominent individuals advocated the unification of Britain and the United States. They dreamt of the final consolidation of the Angloworld. Scholars, journalists, politicians, businessmen, and science fiction writers invested the "Anglo-Saxons" with extraordinary power. The most ambitious hailed them as a people destined to bring peace and justice to the earth. More modest visions still imagined them as likely to shape the twentieth century. Dreamworlds of Race explores this remarkable moment in the intellectual history of racial domination, political utopianism, and world order.Focusing on a quartet of extraordinary figures-Andrew Carnegie, W. T. Stead, Cecil J. Rhodes, and H. G. Wells-Duncan Bell shows how unionists on both sides of the Atlantic reimagined citizenship, empire, patriotism, race, war, and peace in their quest to secure global supremacy. Yet even as they dreamt of an Anglo-dominated world, the unionists disagreed over the meaning of race, the legitimacy of imperialism, the nature of political belonging, and the ultimate form and purpose of unification. The racial dreamworld was an object of competing claims and fantasies. Exploring speculative fiction as well as more conventional forms of political writing, Bell reads unionist arguments as expressions of the utopianism circulating through fin-de-siècle Anglo-American culture, and juxtaposes them with pan-Africanist critiques of racial domination and late twentieth-century fictional narratives of Anglo-American empire.Tracing how intellectual elites promoted an ambitious project of political and racial unification between Britain and the United States, Dreamworlds of Race analyzes ideas of empire and world order that reverberate to this day